The Risk from Anti-Thyroid Hormone Antibody Interference in Neonatal Congenital Hypothyroidism Screening - Ian Brincat; Gerald Buhagiar (MDPI AG, 2017)
Neonatal congenital hypothyroidism screening is considered to be one of the most effective newborn screening strategies. Neonatal screening for congenital hypothyroidism involves the analysis of thyroid hormone and thyrotropin levels using an immunoassay based technique. Immunoassays are also prone to analytical problems such as assay interference. Immunoassays used for thyroid hormone measurement are known to be affected from anti-thyroid hormone antibody interference. This is the first reported case of interference presumably caused by anti-thyroid hormone antibodies transferred from mother to child during pregnancy, affecting the measurement of free-thyroxine in a cord-blood sample. We report a case of a full-term newborn with presumed anti-thyroid hormone antibody interference present in both cord blood and subsequent venous blood samples. In the context of a newborn screening programme based solely on thyroxine measurement, this is an important finding, since it has the potential to cause false negative screening results.